Study of Oral Administrated Silymarin Effects on UV-induced Changes on Albino Guinea Pigs Skin - HR Ahmadi - Ashtiani; MM Naderi; S Bokaii; H Rastegar; Sh Rezazadeh (Institue of Medicinal Plants, ACECR, 2010)
Background: Studies have shown that Silymarin is one of the infrequent herbal materials which have protective effects against sunburn, non melanoma skin cancer and immunosupression in oral administration. Easiness of use, low cost and availability of Silymarin can propose it for use in many topical sunscreen products. Objectives: Regarding to the skin damages caused by the ultraviolet ray of sun and necessity to use of protective agents against mal effects of this ray, in this study the effects of oral use of Silymarin against effects of UV irradiation was evaluated. Methods: In this study 60 albino guinea pigs were selected and they divided in two equal groups. Animals in the experimental group administered 50 mg/kg Silymarin 20 days before and through the irradiation period orally. Control group received distilled water only. Then each group exposed to 180mj/cm2 UV ray. Finally clinical signs were noted and sampling was done from irradiated skin areas for histopathological evaluation. Results: Histopathological and clinical findings showed that oral administration of Silymarin had protective effects against mal effects of UV irradiation on guinea pig skins. Conclusion: The results of this study can be incentive for introduction and use of this herbal agent in sun ray protective oral products because any topical sunscreen has not perfect protective effects against all UV irradiation spectrums.